Cyber negotiation: a cyber risk management approach to defend urban critical infrastructure from cyberattacks. Issue 1 (2nd January 2019) - Falco, Gregory; Noriega, Alicia; Susskind, Lawrence
ABSTRACT: Technical tools dominate the cyber risk management market. Social cybersecurity tools are severely underutilised in helping organisations defend themselves against cyberattacks. We investigate a class of non-technical risk mitigation strategies and tools that might be particularly effective in managing and mitigating the effects of certain cyberattacks. We call these social-science-grounded methods Defensive Social Engineering (DSE) tools. Through interviews with urban critical infrastructure operators and cross-case analysis, we devise a pre, mid and post cyber negotiation framework that could help organisations manage their cyber risks and bolster organisational cyber resilience, especially in the case of ransomware attacks. The cyber negotiation framework is grounded in both negotiation theory and practice. We apply our ideas, ex post, to past ransomware attacks that have wreaked havoc on urban critical infrastructure. By evaluating how to use negotiation strategies effectively (even if no negotiations ever take place), we hope to show how non-technical DSE tools can give defenders some leverage as they engage with cyber adversaries who often have little to lose.